Pilot study on quantitative assessment of muscle imbalance: Differences of muscle synergies, equilibrium-point trajectories, and endpoint stiffness in normal and pathological upper-limb movements - Oku, Takanori; Uno, Kanna; Nishi, Tomoki; Kageyama, Masayuki; Phatiwuttipat, Pipatthana; Koba, Keitaro; Yamashita, Yuto; Murakami, Kenta; Uemura, Mitsunori; Hirai, Hiroaki; Miyazaki, Fumio; Naritomi, Hiroaki (2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society, 2014)
This paper proposes a novel method for assessment of muscle imbalance based on muscle synergy hypothesis and equilibrium point (EP) hypothesis of motor control. We explain in detail the method for extracting muscle synergies under the concept of agonist-antagonist (AA) muscle pairs and for estimating EP trajectories and endpoint stiffness of human upper limbs in a horizontal plane using an electromyogram. The results of applying this method to the reaching movement of one normal subject and one hemiplegic subject suggest that (1) muscle synergies (the balance among coactivation of AA muscle pairs), particularly the synergies that contributes to the angular directional kinematics of EP and the limb stiffness, are quite different between the normal subject and the hemiplegic subject; (2) the concomitant EP trajectory is also different between the normal and hemiplegic subjects, corresponding to the difference of muscle synergies; and (3) the endpoint (hand) stiffness ellipse of the hemiplegic subject becomes more elongated and orientation of the major axis rotates clockwise more than that of the normal subject. The level of motor impairment would be expected to be assessed from a comparison of these differences of muscle synergies, EP trajectories, and endpoint stiffness among normal and pathological subjects using the method.